Alternatives for mammal pest control in New Zealand in the context of concerns about 1080 toxicant (sodium fluoroacetate). Issue 2 (3rd April 2022) - Warburton, Bruce; Eason, Charles; Fisher, Penny; Hancox, Nick; Hopkins, Brian; Nugent, Graham; Ogilvie, Shaun; Prowse, Thomas A. A.; Ross, James; Cowan, Phil E.
ABSTRACT: The ongoing use of 1080 toxin for the control of mammal pests in New Zealand remains highly contentious. Several reviews over the last 25 years identified information gaps and areas of concern, both social and scientific. In this paper these areas of concern are discussed and the extensive scientific and social research that has been undertaken to clarify and address them is reviewed. Although there has been a major national investment in research aimed at finding an alternative to 1080, that has not yet been fully achieved because of low or inconsistent efficacy and/or low cost-effectiveness of alternatives, regulatory difficulties in obtaining approval for aerial delivery of any alternative, and toxic residue concerns. Finding an alternative that has similar efficacy while satisfying the demands for species-selectivity, no residues, and humaneness is a continuing challenge. The most promising prospect appears to be through understanding the genome of the target animals and opportunities for genetic manipulation, either by developing species-specific designer lethal toxicants based on genome mining, or by gene editing to develop non-lethal technologies. Both will require considerable time and funding for research, and considerable effort and engagement to address social and regulatory hurdles.